Revisiting The Impact of Trade Openness and FDI on CO2 Emissions: Evidence from ASEAN-China FTA Countries - Sumiyati, Tatik (Cendekia Niaga, 2025)
The rise of the economy driven by free trade and foreign direct investment (FDI) has implications for environmental degradation, chiefly due to carbon dioxide (CO2) emissions that may induce the greenhouse effect and subsequently contribute to climate change. Climate change resulting from CO2 emissions is presently a worldwide problem and is one of the Sustainable Development Goals (SDGs). Nonetheless, the correlation between trade openness and FDI inflows regarding CO2 emissions remains inconclusive. This study aims to fill this research gap by revisiting the effect of trade openness and FDI on CO2 emissions using panel data from ASEAN countries from 1990 to 2023, using a fixed effects panel regression approach. The findings indicate that trade openness can raise CO2 emissions, and the impact has grown since the introduction of the ASEAN-China Free Trade Agreement. Policymakers can mitigate the negative effects of trade on carbon emissions by implementing comprehensive carbon pricing mechanisms, promoting green trade, improving FDI regulatory frameworks, fostering regional cooperation, and establishing robust monitoring systems.